2021
DOI: 10.3390/su13031519
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive and Antimicrobial Properties of Eggplant (Solanum melongena L.) under Microwave Cooking

Abstract: Fruits and vegetables constitute a considerable amount of antioxidants and among them eggplant is a rich source of polyphenol compounds. This study investigated the bioactive and antimicrobial properties of eggplant under different degree of microwave cooking. The eggplant was cooked for 7 min (light cooked), 10 min (medium cooked), and 15 min (high cooked). The highest total polyphenol content was observed in the light cooked eggplant sample (27.35 mg gallic acid equivalent (GAE)/g dry weight (DW)) followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…The diversity of polyphenolic compounds present in raw eggplant is widely recognized, but in our study, only were confirmed with standards chlorogenic acid, tyrosol and p-vanillin, being chlorogenic the most abundant (37.8 mg GAE/kg f.w.). Compounds found in our study have been previously reported in raw eggplant, additionally to caffeic acid [61], ferulic, and p-coumaric acid [24,62]. Chlorogenic acid is a hydroxycinnamic acid-derivative; this family of phenolics accounts for 95.6% of the total identified phenolic compounds in eggplant [24].…”
Section: Phenolic Profilesupporting
confidence: 77%
See 1 more Smart Citation
“…The diversity of polyphenolic compounds present in raw eggplant is widely recognized, but in our study, only were confirmed with standards chlorogenic acid, tyrosol and p-vanillin, being chlorogenic the most abundant (37.8 mg GAE/kg f.w.). Compounds found in our study have been previously reported in raw eggplant, additionally to caffeic acid [61], ferulic, and p-coumaric acid [24,62]. Chlorogenic acid is a hydroxycinnamic acid-derivative; this family of phenolics accounts for 95.6% of the total identified phenolic compounds in eggplant [24].…”
Section: Phenolic Profilesupporting
confidence: 77%
“…In addition, deep-frying also contributed to p-coumaric acid, ferulic acid, sinapic acid, and quercetin. The phenols added were reported before in the fresh or processed eggplant without oil, as in the case of chlorogenic acid, caffeic acid, and vanillin in fresh and microwaved eggplant [61]; also as in the case of ferulic and p-coumaric acids [24,62]. The concentration of individual phenols found in the fresh vegetable phenolic profile increased with all the culinary techniques tested standing out deep-frying.…”
Section: Phenolic Profilementioning
confidence: 75%
“…These antioxidants can derive from all plant-based ingredients, which are good sources of antioxidants. However, a higher contribution is expected from the eggplant fruits (the content of polyphenols in eggplant was not found to be affected by grilling [29]) and red Florina pepper, since they consist of the larger part of the AS [29][30][31]. Moreover, the results showed that the extracted oil from the salad without preservatives showed the highest (significant at p < 0.05) induction period (higher oxidation resistance), compared to the extracted one from the salad with preservatives.…”
Section: Determination Of Oxidation Stability and Tocopherol Compositionmentioning
confidence: 99%
“…This is indicated that 0.5% eggplant inhibited the deterioration of protein in patties. Salamatullah et al (2021) have found that fresh and cooked EP had an ability to inhibit the growth of Staphylococcus aureus, Listeria monocytogenes, Escherichia coli, Pseudomonas aeruginosa and Candida albicans.…”
Section: Volatile Basic Nitrogen (Vbn)mentioning
confidence: 99%